Upaya Pendampingan Pijat Laktasi Pada Ibu Nifas Terhadap Bayi Usia 0-6 Bulan Di Desa Topoyo - Parwati, Dewi; Susanti, Susanti; Thalib, Kiki Uniatri; Sallo, Andi Kamal M (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Lactation massage is an action to help produce more breast milk and prevent swelling of the breasts during the breastfeeding process. Breast milk production can be influenced by two factors, namely production and expenditure. This PkM aims to determine whether or not there is an effect of lactation massage on breast milk production in post partum mothers and Exclusive Breastfeeding guarantees the fulfillment of the baby's right to receive exclusive breastfeeding from birth until 6 months of age by paying attention to its growth and development. Some mothers may have difficulty expressing breast milk because more mothers are influenced by myths so that mothers are not sure they can give breast milk to their babies. The role of the midwife here is as implementer, manager, educator, researcher, empowerer and advocate. One of the midwives' roles during the postpartum period is to make home visits at least 3 times to monitor the condition of the mother and baby after giving birth and ensure that the baby is given exclusive breast milk. Apart from making home visits, the midwife's role is also to provide counseling, counseling and outreach regarding proper breast care through lactation massage. The target of the program that will be carried out is to improve the health of mothers and babies by providing outreach about lactation massage to facilitate breast milk production. The resulting program output is an increase in the health status of mothers and babies.